Discussion board assignments and their impact on creating engaged learning environments in art history online courses - Ter-Stepanian, Anahit (Handbook of Research on Didactic Strategies and Technologies for Education: Incorporating Advancements, 2013)
The adaptation of traditional, face-to-face courses to the online format presents both challenges and opportunities. Many pedagogical practices need to be rethought when designing online courses. A successful online course needs to be intellectually stimulating and engaging. The chapter demonstrates how to create an engaging learning environment without any additional budget. The author describes approaches that she has developed, experimented with, and found to be effective in asynchronous online art history courses, as well as learner engagement strategies she has implemented in the eLearning environment. Advantages of scenario-based discussions board assignments and the effects of role playing in discussion forums are discussed. The author shares examples of personalized discussion board assignments aimed to motivate online learners, create a collaborative learning environment, improve peer-to-peer interaction, and prevent plagiarism.
Keywords: dept.art